Relationship of Interfaith in Tunisia (Critical Study of Ibn ‘Ashur Tafsir W.1973) - Amiur Nuruddin; Ahmad Qarib; Azwani Lubis; Muhammad Faisal Hamdani (Budapest International Research and Critics University, 2019)
Relations between Muslims and non-Muslims will often experience disruption / friction if not addressed wisely, especially in terms of social politics, the order of social life. In Islam, Religion and Politics two things are difficult to separate. This often becomes a polemic to produce many interpretations and frictions in various regions and majority Muslim countries. Interpretation of the Qur'anic verses relating to religious and political relations also has a variety of colors and patterns which in the end can also produce identity theory in the practice of life. This paper aims to look at the opinion of Ibn Atsur in terms of the relationship / relationship between Islam and non-Islam, in what way and practice how Muslims and non-Muslims can work together and coexist and in terms of what and how they should be separated. Writing that uses this character qualitative method tries to look at the data based on Ibn Atsur's interpretation in his book